PELATIHAN DAN PENDAMPINGAN PENGGUNAAN KIT IPA DI SD NEGERI 34 CAKRANEGARA - Baiq Niswatul Khair; Fitri Puji Astria; K. Sri Kusuma Wardani; Nurwahidah Nurwahidah; N L P. Nina Sriwarthini; Aisa Nikmah Rahmatih (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2021)
The Ministerial Regulation on Basic and Secondary Education Process Standards ensures that the learning process in primary education should be enjoyable. Fun learning can be obtained through scientific-based learning such as practicum or business. But in reality, learning is conventional, namely lectures and discussions. The utilization of sciences KIT as a learning medium that is owned is never used in classroom learning activities. This is shown from the sciences KIT which is still neatly stored and looks dusty. The reason the sciences KIT was not used was because of the inability of the teacher because they had never received training and the training would damage the sciences KIT used so that the teacher preferred to use conventional learning methods and media. The strategy carried out in this service uses several methods of lectures and presentations, question and answer/discussion, and mentoring. Activities that have been implemented can be said to run smoothly according to the planned schedule. There are no obstacles and problems during the activity and all team members can attend every activity. The whole series of activities starting from the opening stage, delivering training materials, training to closing went smoothly without any meaningful school.